Observations on the relationship between the size of maxillary sinus detected on panoramic radiography and dental pathology - Grigorescu Catalin Cicerone; Stanciu Dan; Stanciu Radu; Temelcea Anca (Medicamentul Veterinar)
The pathology of the teeth sinus (which by their apexes established direct neighborhood reports with maxillary sinus) is a sensitive subject of modern dentistry. The implications of these neighborhood reports, it rests in establishing a treatment plan aimed at various fields of dentistry. If we were to detail, reports of the teeth sinus with maxillary sinus floor limit insertion of dental implants, for example, conditioning this therapeutic maneuver with combination or not with sinus elevation (process known as sinus lifting). In orthodontics, on the other hand, the presence of the maxillary sinus that is inserted through the roots of the teeth in lateral displacement limit the scope of the mesial-distal and / or in the vertical plane of these teeth in the remaining size of the alveolar bone, which allows the processes of absorption and bone in growth. Finally, sinus tooth apical processes, acute or chronic, often have echo in sinus pathology, which requires the patient to early orientation ENT service. Given all these considerations, an accurate determination of the size of the maxillary sinus panoramic radiography submit undeniable benefits in terms of establishing a treatment plan, limiting the maximum uncertainties related reports sinus tooth neighborhood.